Future-proof your school : steering culture, driving school improvement, developing excellence. - Hughes, David W. (Practical teaching, 2019)
Wouldn't it be great if you could equip your school and yourself to face whatever the future might throw at you! Wherever you are in your teaching career, this book provides an effective approach to change management that is simple and sustainable.